Clinical Characteristics of Patients with Coronavirus Disease (COVID-19): Preliminary Baseline Report of Japan COVID-19 Task Force, a Nationwide Consortium to Investigate Host Genetics of COVID-19. (December 2021) - Tanaka, Hiromu; Lee, Ho; Morita, Atsuho; Namkoong, Ho; Chubachi, Shotaro; Kabata, Hiroki; Kamata, Hirofumi; Ishii, Makoto; Hasegawa, Naoki; Harada, Norihiro; Ueda, Tetsuya; Ueda, Soichiro; et al.
Highlights: Patients with COVID-19 were recruited from more than 70 institutes in Japan. Japan experienced 3 waves of COVID-19 during the first year of the pandemic. The case fatality rate of 3.2% was relatively low. The data will be used for a genome-wide association study. Abstract: Background and design: The coronavirus disease (COVID-19) pandemic is having a devastating effect worldwide. Host genome differences between populations may influence the severity of COVID-19. The Japan COVID-19 Task Force is conducting host genome analysis of hospitalized patients with COVID-19 from more than 70 institutions nationwide in Japan. This report describes the clinical characteristics of patients enrolled to date. Results: The median (interquartile range) age of the 1674 patients included in the analysis was 59 (45–71) years, and more than half of the patients (66.2%) were male. Less than half of the patients (41.2%) had severe disease. The case fatality rate was 3.2%. Conclusions: Since this is a hospital-based study, the number of severe cases was relatively high, but the case fatality rate was relatively low, when compared to that of other countries. In the future, we will continue to enroll patients and conduct genome analyses of patients with COVID-19.